EDUCATIONAL RESILIENCE AND THE RISK OF MENTAL DISORDERS - Oprea-Valentin BUŞU; Elena-Cristina ANDREI (Universitaria Publishing House, Craiova, 2022)
Educational resilience is a complex subject, insufficiently addressed. The concept of educational resilience refers to the student's ability to overcome stressful events in an optimal way. We often observe how students with very good academic results end up developing depressive or anxious states as a result of a stressful event or as a result of a situation with a high degree of difficulty. Our study aims to highlight the following aspects: the frequency of difficult situations faced by first year students from the University of Medicine and Pharmacy of Craiova and the University of Craiova, the degree of resilience approached in terms of time needed to overcome a stressful event, students' ability to recover, the level of stress perceived by students during the exam session, the possibility of the idea of interrupting studies, the degree of motivation for the chosen field of study, the availability of students to participate to a course of emotion management in stressful periods. The study was conducted using a questionnaire covering 15 questions with a simple complement on a sample of 89 students. We believe that the results obtained from this study will contribute significantly to the awareness of the importance of the phenomenon of educational resilience. The causes that often lead to academic failure or dropping out of school are directly proportional to the student's degree of resilience.